Analytical Advantages of Electrodeposition for Determination of Cadmium by Atomic Absorption Spectroscopy - Salar Amoli, H.; Barker, J. (Asian Journal of Chemistry, 2010)
This work utilizes preconcentration of the cadmium in environmental samples by electrodeposition technique prior to its determination by flame and furnace atomic absorption spectroscopy. Using the method it is possible to reduce detection limits in the range of μg/mL for flame AAS and ng/mL for graphite furnace (GF-AAS) and the sensitivity improvements ranging from 8-15 fold have been obtained. The effect of the deposition time and thickness was investigated and optical microscope studies show that a thickness of 25-40 micron gives the best results. By the method describe here, matrix interferences could be overcome and quantitative deposition of cadmium onto the electrode for 15-25 min at the 5-7 V is achieved.